Comparing the accuracy and complications of peripherally inserted central catheter (PICC) placement using fluoroscopic and the blind pushing technique. Issue 4 (3rd August 2021) - Erskine, Brendan; Bradley, Pierre; Joseph, Tim; Yeh, Sabrina; Clements, Warren
Abstract: Introduction: Peripherally inserted central catheters (PICCs) offer a convenient long‐term intravenous access option. Different methods exist for insertion including the use of continuous fluoroscopy for guidance, or bedside insertion techniques. The blind pushing technique is a bedside approach which involves advancing a PICC through the access sheath without imaging guidance, before taking a mobile chest radiograph to confirm tip position. Obtaining optimal position is a critical aim of PICC placement as malpositioned lines have been associated with higher complications including death. We aimed to assess the accuracy of PICC placement by comparing the tip position and complications for lines placed under fluoroscopic guidance to those placed without fluoroscopic guidance. Methods: The Radiology Information System was used to identify 100 continuous PICC insertions in each group (fluoroscopic and blind pushing) between 1 January and 12 May 2019. Patients were excluded if there was a known history of central venous occlusion/stenosis. Results: In the fluoroscopic‐guided group, 0% of the lines were malpositioned compared with 60% of the lines placed using the blind pushing technique, P  < 0.001. Fluoroscopic‐guided PICC insertions were in place for a total of 2446 days and demonstrated 6 complications (2.45 complications per 1000 catheter days). This compared with blind pushing technique PICC insertions which were in place for a total of 1521 days and demonstrated 18 complications (11.83 complications per 1000 catheter days), P  = 0.004. Conclusion: The use of fluoroscopy for PICC placement leads to significant improvements in tip accuracy than for PICCs placed using the blind pushing technique. While the use of these imaging resources incurs cost and time, these factors should be balanced in order to offer patients the safest and most accurate method of line insertion. Abstract : Different methods exist for insertion of PICCs. 200 PICCs were assessed for malposition and consisted of 100 fluoroscopic‐guided and 100 using a blind pushing technique at the bedside. In the fluoroscopic‐guided group, 0% of the lines were malpositioned compared with 60% of the lines placed without fluoroscopic guidance, P  < 0.001. While the use of fluoroscopy incurs cost and time, these factors should be balanced in order to offer patients the safest and most accurate method of line insertion.